2013
DOI: 10.1007/s00221-012-3370-7
|View full text |Cite
|
Sign up to set email alerts
|

Motivation from control

Abstract: Human motivation is sensitive to value-to the outcomes of actions. People invest mental and physical resources for obtaining desired results or for stopping and reversing undesired ones. Accordingly, people's motivation is sensitive to information about their standing in relation to outcome attainment ('outcome feedback'). In this paper, we argue and present the first evidence for the existence of another motivational sensitivity in humans-a sensitivity to our degree of control on the environment and hence to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
122
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(146 citation statements)
references
References 39 publications
23
122
0
1
Order By: Relevance
“…These findings are consistent with various postulations that agency is itself rewarding, motivating, and desirable. The results also fit well with previous work from our lab (Eitam et al, 2013) using another task, in which we found that participants' correct responses are faster when they are immediately followed by an effect (compared to when Participants' chose the key associated with the highest probability of delivering an effect reliably more often than they chose the key that never delivered one in both conditions. no such effect appeared or when they were followed by a 300 ms lagged effect).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These findings are consistent with various postulations that agency is itself rewarding, motivating, and desirable. The results also fit well with previous work from our lab (Eitam et al, 2013) using another task, in which we found that participants' correct responses are faster when they are immediately followed by an effect (compared to when Participants' chose the key associated with the highest probability of delivering an effect reliably more often than they chose the key that never delivered one in both conditions. no such effect appeared or when they were followed by a 300 ms lagged effect).…”
Section: Discussionsupporting
confidence: 90%
“…Two extant studies lend direct support to the prediction that valance-neutral own-action-effects do in fact increase motivation (Eitam, Kennedy, & Higgins, 2013;Stephens, 1934) but unfortunately, in both the mere exercise of control was not clearly dissociated from information about obtaining desired outcomes (e.g., successful task performance). As such, even the simple question of whether mere agency motivates in and of itself is still wide open.…”
Section: Judgment Of Agency Affects Action Selectionmentioning
confidence: 88%
“…uncover the full range of cognitive mechanisms influenced by control and truth motivations (see Eitam, Kennedy, & Higgins, 2013;Higgins, 2012b). Even though our study cannot address all of these aspects, the multi-phase-multi-sample design we employed enables us to identify some of the likely causes of the poor fit associated with the original scales.…”
Section: Discussion Directions For Future Research and Conclusionmentioning
confidence: 99%
“…Studies with both humans (Tiger, Hanley, & Hernandez, 2006) and other animals (Catania, 1975;Catania & Sagvolden, 1980;Voss & Homzie, 1970) have shown that both prefer an option leading to a choice than an option that does not, even if this option results in greater effort or worksuggesting the existence of an inherent reward with the exercise of control (Karsh & Eitam, 2015;Leotti & Delgado, 2011). Along the same lines, Eitam, Kennedy, and Higgins (2013) demonstrated that human motivation is dependent on (the perception of) one's actions having effects on the environment. Even if the effects of one's actions are trivial, intrinsic motivation is enhanced if the performer has control over those effects (termed Control Effect Motivation by Eitam et al).…”
Section: Autonomymentioning
confidence: 99%